La Réaction Des Cours Boursiers Suite À Une Nouvelle Annonce Des Entreprises: Cas De La Bourse Régionale Des Valeurs Mobilières (BRVM) - Guilaire, Dadem Kemgou, Edouard; Lord, Manetsa, Eloge; Léopold, Djoutsa Wamba,; David, Kamdem, (European Scientific Journal, ESJ, 2017)
The purpose of this article is to highlight the reaction of share prices following the publication of dividends on the regional stock exchange (RSESS). To achieve the objective of our study, daily profitability series data were used over the period from January 1998 to December 2007. The methodology of the event studies was used and there are various ways to incorporate the "Event in the prices. It is accepted that the effect of the announcement of the dividend for all the securities is positive despite imperfections in the reaction of the markets. Consequently, the publication of dividends has an impact on stock market returns. The hypothetical information content of the dividend (ICHD) is therefore accepted.